Improved preimage and pseudo-collision attacks on SM3 hash function - Jian ZOU; Le DONG (Tongxin xuebao)
A preimage attack on 32-step SM3 hash function and a pseudo-collision attack on 33-step SM3 hash function respectively were shown.32-step preimage attack was based on the differential meet-in-the-middle and biclique technique,while the previously known best preimage attack on SM3 was only 30-step.The 33-step pseudo-collision attack was constructed by using the same techniques.The preimage attack on 32-step SM3 can be computed with a complexity of 2254.5,and a memory of 25.Furthermore,The pseudo-preimage and pseudo-collision attacks on 33-step SM3 by extending the differential characteristic of the 32-step preimage attack were present.The pseudo-collision attack on 33-step SM3 can be computed with a complexity of 2126.7,and a memory of 23.